Legal issues and underexplored data protection in medical 3D printing: a scoping review - Pettersson, Ante B.; Ballardini, Rosa Maria; Mimler, Marc; Li, Phoebe; Salmi, Mika; Minssen, Timo; Gibson, Ian; Mäkitie, Antti (Frontiers Media, 2023)
Funding Information: AP is supported by grants from the Viipuri Tuberculosis Foundation, the South-Karelia Medical Association, the Emil Aaltonen Foundation and the Finnish Medical Foundation. PL is supported by the UKRI Strategic Priorities Fund to the UKRI Research Node on Trustworthy Autonomous Systems Governance and Regulation (EP/V026607/1, 2020–2024) and the Leverhulme Trust ‘Biomodifying technologies: governing converging research in the life sciences’ (grant number 68387). MS is supported by the Academy of Finland (grant numbers 325509 and 352438). RB has received funding from the project “Shaping, Fixing, and Making Markets via IPR: Regulating Sustainable Innovation Ecosystems (SHARE)”, funded by the Academy of Finland (decision number 332819). TM’s research for this contribution was supported by a Novo Nordisk Foundation for a scientifically independent Collaborative Research Programme in Biomedical Innovation Law (grant agreement number NNF17SA0027784). Publisher Copyright: Copyright © 2023 Pettersson, Ballardini, Mimler, Li, Salmi, Minssen, Gibson and Mäkitie. Introduction: 3D printing has quickly found many applications in medicine. However, as with any new technology the regulatory landscape is struggling to stay abreast. Unclear legislation or lack of legislation has been suggested as being one hindrance for wide-scale adoption. Methods: A scoping review was performed in PubMed, Web of Science, SCOPUS and Westlaw International to identify articles dealing with legal issues in medical 3D printing. Results: Thirty-four articles fulfilling inclusion criteria were identified in medical/technical databases and fifteen in the legal database. The majority of articles dealt with the USA, while the EU was also prominently represented. Some common unresolved legal issues were identified, among them terminological confusion between custom-made and patient-matched devices, lack of specific legislation for patient-matched products, and the undefined legal role of CAD files both from a liability and from an ...